2007
DOI: 10.1177/172460080702200102
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conserved Sequence of Exon 15 BRAF Gene and KRAS Codon 12 Mutation among Greek Patients with Colorectal Cancer

Abstract: Despite the limited study sample, our data suggest that BRAF mutations might be present less frequently than KRAS mutations in Greek patients with colorectal carcinomas. Further research involving larger patient series will be necessary to confirm these findings and to assess possible ethnic, environmental and lifestyle influences on BRAF and KRAS mutagenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…When RAS family members become activated, through physiological stimuli or through mutation [7], [17], [42], [43], they signal to key pathways involved in cell growth, survival, differentiation and migration, including the RAF-MAPK [44], PI3K [45], and the RALGEF (RALGDS; ral guanine-nucleotide-dissociation stimulator) [46] pathways. In non-muscle invasive BC, HRAS has been shown to be the most commonly mutated RAS family oncogene [7], [47], [48].…”
Section: Discussionmentioning
confidence: 99%
“…When RAS family members become activated, through physiological stimuli or through mutation [7], [17], [42], [43], they signal to key pathways involved in cell growth, survival, differentiation and migration, including the RAF-MAPK [44], PI3K [45], and the RALGEF (RALGDS; ral guanine-nucleotide-dissociation stimulator) [46] pathways. In non-muscle invasive BC, HRAS has been shown to be the most commonly mutated RAS family oncogene [7], [47], [48].…”
Section: Discussionmentioning
confidence: 99%
“…It is of note now that smoking is involved in the pathogenesis of pulmonary fibrosis and influences the outcome [41]. Moreover, smoking and other environmental agents also have a negative effect on innate immunity and various cancers [42]. It has been observed that the expression of TLR-2 and -4 in alveolar macrophage of smokers in response to their ligands is decreased compared to nonsmokers [43].…”
Section: Discussionmentioning
confidence: 99%
“…One study in France (Chretien et al, 2013) reported KRAS mutations in 82.4% happened in codon 12 and 17.6% in codon 13. In sixty-one cases selected from the Greek population, the frequency of the mutation in the codon 12 was 28.3% (Symvoulakis et al, 2007). Mutation status in codon 12 and codon 13 were 62.2% and 21.4% (Miglio et al, 2013).…”
Section: Discussionmentioning
confidence: 99%